Treatment of relapsed/refractory multiple myeloma with thalidomide-based regimens: Identification of prognostic factors - Anagnostopoulos, A.; Gika, D.; Hamilos, G.; Zervas, K.; Zomas, A.; Pouli, A.; Zorzou, M.; Kastritis, E.; Anagnostopoulos, N.; Tassidou, A.; Anagnostou, D.; Dimopoulos, M.-A. (Leukemia and Lymphoma, 2004)
We evaluated the predictive value of several parameters, including the International Staging System (ISS) for myeloma, in patients with advanced disease treated with thalidomide-based regimens (TBR). We analyzed 119 patients, from 3 phase II studies. Patients with pretreatment β2 microglobulin < 3.5 mg/l and albumin ≥ 3.5 g /dl were scored ISS stage 1, patients with β2 microglobulin < 3.5 mg/1 and albumin < 3.5 g/dl or β2 microglobulin 3.5-5.5 mg/l regardless of albumin levels were scored ISS stage 2, patients with β2 microglobulin > 5.5 mg/l ISS stage 3. ISS stage was 1, 2 and 3 in 45, 32 and 23% of patients respectively. Seventy-four patients (62% achieved at least partial response. Median progression-free and overall survival were 8 months and 19.5 months respectively. ISS stage, serum LDH and performance status were independent predictive factors for survival. Based on these 3 variables a scoring system was developed with survival times of 38.1, 28.8 and 5.8 months for scores 0, 1 and 2 respectively. The ISS staging system was highly predictive for overall survival of patients with advanced myeloma treated with TBR. With the addition of performance status and serum LDH, a simple scoring system was developed which may help select patients likely to benefit from TBR. © 2004 Taylor & Francis Ltd.
Keywords: Advanced myeloma; International Staging System; Prognostic factors; Staging